Gut Microbiome and Diabetes: Emerging Perspectives in Metabolic Regulation - Kaur, Navreet; Kaur, Navjot; Verma, Aanchal; Sharma, Rahul Kumar (Scripta Medica, 2026)
Diabetes mellitus Type 2 (T2DM) is one of the fastest-growing metabolic disorders in the world. It is marked by insulin resistance, high blood sugar and high cholesterol levels. Recently, its prevalence has increased significantly, making it a major health issue globally. New evidence shows that people with T2DM often have changes in their gut microbiota composition and suffer from problems in multiple organ systems. This review focused on the changes in gut microbiota related to T2DM and examines how microbial byproducts affect the disease's development. The potential for identifying at-risk individuals based on microbial patterns and the creation of specific treatments was also discussed. Lastly, it was looked into gut health strategies that aim to change the gut microbiota to prevent or slow the advancement of T2DM.